TEACHING THE SUBJECT "GALAXY STRUCTURE, COMPOSITION AND ROTATION" USING THE "SWOT-ANALYSIS" METHOD (ResearchJet Journal of Analysis and Inventions, 2023)
The article describes the advantages of the "SWOT-analysis" method in teaching the topic "Galaxy structure, composition and rotation".